Are the challenges we face with Climate Change greater than the challenges of the Green Revolution? - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Interview with Pramod Aggarwal of the Indian Agricultural Research Institute. Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya